PENELUSURAN SPESIMEN HERBARIUM DALAM JARINGAN - Putu Gede P. Damayanto, I; Surya Dwipa Irsyam, Arifin (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2022)
In this technological era, some institutions in the world have scanned herbarium specimens into images and stored them in special portals. This makes it easier for researchers to access various collections spread all over the world. This study aimed to provide information about the online database portals that provide scanned images of herbarium specimens. The study was conducted by compiling the online database portals that provide scanned images of herbarium specimens in a matrix and then was scored to give recommendations for selecting a priority portal. The data were analyzed and described descriptively. This study showed that there are 13 online database portals that provide scanned images of herbarium specimens, namely portals of Australasian Virtual Herbarium (AVH), BioPortal: Browse Dutch Natural History Collections (BioPortal), e-ReColNat, Global Biodiversity Information Facility (GBIF), Kew Herbarium Catalogue (HerbWeb), Integrated Digitized Biocollections (iDigBio), JACQ Virtual Herbaria (JACQ), JSTOR’s Global Plants (JSTOR), MNHN Vascular Plants (P), NYBG C. V. Starr Virtual Herbarium, Plants of the World Online (POWO), Reflora Virtual Herbarium (Reflora), and Tropicos. The thirteen portals have characteristics (features) that are different from one another, not all of them provide fully open (free) access, scanned images of herbarium specimens downloaded are varied, and the availability of a feature for real-time observation of scanned herbarium specimens.